2017
DOI: 10.18632/oncotarget.22530
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EGFR and KRAS gene mutations using suspension liquid-based cytology specimens in metastatic lung adenocarcinoma

Abstract: BackgroundThe detection of EGFR and KRAS mutations of metastatic lung adenocarcinoma using liquid-based cytology suspension routine specimens from fine-needle aspiration remains controversial.ResultsThe DNA of all specimens was extracted and real time PCR was performed successfully. The rate of EGFR and KARS mutations was 37.7% (58/154) and 5.8% (9/154), respectively. EGFR mutation rate was significantly higher in females than that in males (47.8% vs. 29.4%, P = 0.019). There were no significant differences am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…However, even when the sampling is not cytological but histological (e.g., endobronchial forceps biopsy, core needle biopsy) the agile cytopathologist can employ quick cytological techniques for rapid on-site evaluation and specimen triage [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Small biopsies can be used to prepare the whole array of cytological specimens in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…However, even when the sampling is not cytological but histological (e.g., endobronchial forceps biopsy, core needle biopsy) the agile cytopathologist can employ quick cytological techniques for rapid on-site evaluation and specimen triage [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Small biopsies can be used to prepare the whole array of cytological specimens in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…All the materials in the current study were fixed using CytoRich Red, and these fixed materials appeared to be suitable for molecular detection studies. The ThinPrep method (Hologic, Bedford, Massachusetts) has also recently been used to determine the suitability of LBC using other fixative techniques for molecular testing in our institution. Furthermore, we should examine the optimal preparation conditions for diagnosis and molecular testing in a clinical setting, and further studies are needed to compare the results of detection using bronchoscopic LBC materials with the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…28 All the materials in the current study were fixed using CytoRich Red, and these fixed materials appeared to be suitable for molecular detection studies. The ThinPrep method (Hologic, Bedford, Massachusetts) 29 has also recently been used to determine the suitability of LBC using other fixative techniques for ships between radiological findings on CT and PET and EGFR or KRAS gene mutational status, but found no correlations. 30,31 In contrast, Chiu et al 32 reported that solid ADCs had a significantly higher SUVmax than other subtypes (papillary, acinar, and lepidic) and that tumors with a solid growth pattern showed a significantly higher SUVmax than those without a solid growth pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid-based cytology (LBC) is a useful method for the cytological diagnosis-based screening of lung cancer using sputum and bronchoalveolar lavage, because of its high precision and the availability of automatic standard systems that combine morphological assessment and molecular analyses [4][5][6][7][8][9]. The remaining fixed cells can be used for molecular analysis by extracting nucleic acids such as DNA or RNA for advanced studies.…”
Section: Introductionmentioning
confidence: 99%